Synthesis, characterization and biological activities of organotin (iv) complexes with hydrazone/thiocarbohydrazone ligands - Dayang Norafizan, Awang Chee (Universiti Malaysia Sarawak (UNIMAS), 2012)
Biological study found that green mussels feed on zooplankton, phytoplankton, algae, detritus and partial digested food ranging from 47.5-61.2%, 20.8-27.8%, 7.6-9.7%, 4.1-8.7% and 2.6-14.5% for males and 47.8-58.3%, 20.8-24.8%, 7.2-9.1%, 5.2-8.4% and 5.8-11.7% for females in the Bay of Bengal and 51.2-55.6%, 21.7-23.4%,8.1-8.7%,7.2-7.7% and 6.8-9.7% for males and 51.4-56.2%, 20.9~23.8%, 7.1-8.1%, 7.1-7.7% and 7.6-12.6% for females respectively in the Santubong River. The green mussel exhibits two spawning periods where temperature regulates the onset of reproductive events. Spat settlement densities are greater in the Bay of Bengal than the Santubong river waters. In rope culture mussel attains a marketable size of 50-60 mm in 6 months with an annual production of 47 kg mol in the Bay of Benga9 The asymptotic length (Loo), growth co-efficient (K) and growth performance index (¢) were calculated as 11.55-13.65 cm., 0.97-1.80 yea(l and 2.17-2.53 respectively in the Bay of Bengal and 9.45 cm., 1.10 yea(1 and 1.99 respectively in the Santubong River. The recruitment pattern was found continuous, displaying a double major peak event per year. The exponent 'b' value estimated was below 3 (b<3) indicating that the growth pattern showed negative allometric growth. The effects of anthropogenic activities on the accumulation of heavy metals in green mussel were examined to find out the risk assessment of Cd, Pb, Zn, Cu, Mn and Fe .. The degree of contamination (Cd) was estimated for each site and the data indicate that the green mussel sample demonstrate various degree of metal accumulation and can be used as indicators for the type and quantity of anthropogenic contamination in marine ecosystems. To be more specific, high concentrations Cd, Pb and Mn determined in the Bay of Bengal sites v may indicate a fresh and continuous contamination from domestic and industrial discharges and show that the ecosystem of Bay of Bengal coast is facing heavy metal pollution. The results obtained from the experimental set up in laboratory were found that the concentration of Cu in Chaetoceros sp., green mussels and faecal materials in Cu (15 ~gCulL) contaminated tanks were 56.96 ± 1.87 ~g/g dry wt, 19.08 ± 1.57 ~g/g and 141.90 ± 4.84 1lg/g compared to non-contaminated tanks were 17.79 ± 0.95 ~g/g, 13.36 ± 0.93 Ilg/g and 39.08 ± 1.63 Ilg/g respectively. To determine the depuration some of green mussels were transferred from contaminated tanks to control tanks. The result showed that average concentration of Cu in green mussels continuously decreased from 18.26 ± 1.37 ~g/g to 15.62 ± 1.15 ~g/g dry wt within 48 hours. AHP was applied to evaluate the preference on management objectives and options by stakeholders' participation in decision analysis. "Sustainable mollusc fishery management" was set as a goal in the decision-tree. Considering underlying criteria of "better quality of life", the "reduced conflicts" was chosen as the most priority. To achieve each of these objectives, a number of strategies were formulated with actions and responsible agencies.